The Anthropocene : 101 questions and answers for understanding the human impact of the global environment - Turner, B. L. (Billie Lee), 1945- (Agenda Publishing, 2023)
An authoritative desk-top reference work for students of geography, the environment and sustainability, which through a series of 101 interconnected questions and answers spanning ten thematic sections, provides a comprehensive survey of humankind's impact on the global environment from the Late Stone Age to the present day.